Modelos de branas em gravidades teleparalelas modificadas - Moreira, Allan Ranieri Pereira (2022)
Braneworld models are interesting theoretical and phenomenological frameworks for seeking new physics beyond the standard model of particles and cosmology. In this thesis, we discuss models of braneworlds whose gravitational dynamics are governed by modified teleparallel gravities. In particular, we explore the theories of gravity f(T), f(T,B) and f(T, T ), where T is the torsion scalar, B is the boundary term and T is the energy-momentum tensor trace. In both cases, we observed that„ asymptotically, the geometry of the bulk converges to a space-time AdS5 whose cosmological constant is produced by parameters that control the deviation of the usual teleparallel gravity. Energy density analysis reveals a process of brane splitting satisfying both weak and strong energy conditions. Furthermore, we investigated the behavior of gravitational perturbations. The gravitational modification generates a shift in massive modes with respect to the core of the brane, maintaining a stable, non-localizable tower and producing more localized massless modes. To study the brane-world scenario in gravity f(T, T ), we use first-order formalism to find analytical solutions for models that include a scalar field as a source. In addition, we studied the effects of f(T) and f(T,B) gravities on the location of 1/2 spin fermions in the brane-world scenario. For f(T), we assume a non-minimal coupling between the fermion and the torsion. For f(T,B), we assume Yukawa coupling, where a scalar field is coupled to a Dirac spinor field. We show how the model parameters control the width of the massless Kaluza-Klein mode, the breadth of non-normalized massive fermionic modes, and the properties of the potential near the origin. Furthermore, we use the concept of Differential Configurational Entropy (DCE) to study phase transitions, internal structures and new classes of solutions in our models. DCE has the ability to predict the existence of phase transitions through critical points, being able to select the most stable solutions, as it provides us with details about the informative content of the field configurations. Finally, we extend our study in a gravity f(T) to models with axial symmetry of co-dimension 2, also known as string-like braneworld. Likewise, in the 5D domain-walls models, the modified teleparallel gravities leads to a phase transition on the perfect fluid source providing a brane-splitting mechanism, leading to ring-like structures. Furthermore, gravitational modification alters gravitational perturbations, producing new potential wells within the brane core, leading to a more localized massless mode around ring structures.